Effects of combined general anesthesia and thoracic epidural analgesia on cytokine response in patients undergoing laparoscopic cholecystectomy - Ozcan, S.; Ozer, A. B.; Yasar, M. A.; Erhan, O. L. (Medknow Publications & Media Pvt Ltd, 2016)
Background: Severe postoperative pain is not often experienced in laparoscopic cholecystectomy. Anesthesia, surgery, and pain are stressful and cause different reactions in neuro-immuno-endocrine systems. Many factors such as the pharmacological effect of the drugs used, as well as the type and depth of anesthesia, can affect these reactions. Objective: The aim of this study was to evaluate the effect of the combination of general anesthesia and thoracic epidural analgesia (TEA) on cytokine reaction in laparoscopic cholecystectomy. Study Design: Prospective, randomized clinical comparative study. Materials and Methods: Sixty adult patients scheduled for elective laparoscopic cholecystectomy were divided into four groups. Group saline (Group S), group fentanyl (Group F), group bupivacaine (Group B), and group levobupivacaine (Group L) were infused with saline, saline and fentanyl, bupivacaine and fentanyl, and levobupivacaine and fentanyl, respectively, via epidural catheter before surgical incision. Results: There were no differences among groups in the demographic features, heart rate, mean arterial pressure, and peripheral oxygen saturation values. Group L had lower visual analogue scale value compared to the other postoperative groups (P 0.01). In all groups, interleukin-6 (IL-6), IL-8, and IL-10 levels started to increase at 2 h and returned to the basal level at 24 h. IL levels increased in most of the epidural saline-administered group compared to other groups (P 0.05). Conclusion: Combined general anesthesia and TEA provided pain control and hemodynamic stability more efficiently during the first 24 h of the intraoperative and postoperative period by suppressing cytokine levels. However, we determined that this effect was more obvious with the local anesthetic and opioid combination.
Keywords: Bupivacaine; combined-general-epidural anesthesia; inflammatory cytokines; laparoscopic cholecystectomy; levobupivacaine